Process of strategic management by innovative projects - K. R. Bibarsov (Путеводитель предпринимателя, 2020)
In the article process of strategic management of innovative projects is provided. The methodology of development the system of strategic management instruments of innovative projects which will allow to increase efficiency of decision making in development of social and economic systems is considered.